Antioxidants as stabilizers of UV filters: an example for the UV-B filter octylmethoxycinnamate - Lorigo, Margarida (2019)
Background: Sunlight is one of the main harmful exogenous factors that induce the reactive oxygen species formation. The human skin is the first line of photoprotection against harmful exogenous factors, such as UV radiations. The topical application of sunscreens, containing UV-B filters, is widely used to protect against UV-induced damage. Octylmethoxycinnamate is the world’s most widely used UV-B filter in sunscreens. However, recent studies have demonstrated that this substance is an endocrine disruptor compound and with potential to damage DNA. Thus, the safety of this organic filter is a current concern for human health, and it was urgent to develop new photoprotective strategies. In this sense, due to the potential to neutralize the UV-induced free radicals, the use of antioxidants as UV filter stabilizers presented as a novel promising strategy. Research: The purpose of this review was to assess the use of antioxidants as stabilizers for UV-B filter octylmethoxycinnamate. For this, we discuss the chemical and physical characteristics of UV-B filter octylmethoxycinnamate, emphasizing the stability, photostability, and reactivity of this UV filter. The use of antioxidants in sunscreens will also be addressed, from a perspective of the main characteristics that allowed their use in sunscreen formulations. Then, the concomitant use of both was described from a historical and physical chemical perspective, always emphasizing the advantages and disadvantages of this association. Conclusions: The combination of antioxidants with UV-B filter octylmethoxycinnamate in appropriated formulations represents a viable strategy to protect the human skin against UV-induced damage.